New technology, changing pedagogies? Exploring the concept of remote teaching placement supervision. Issue 1 (1st January 2017) - Chilton, Helen; McCracken, Wendy
Abstract: Mobile technologies continue to have a growing influence on contemporary society, are becoming more commonplace within tertiary educational settings and hold the potential to impact on the learning process. This project evaluation considers the perspectives of participants who trialled the use of new technology to enable remote supervision and assessment of situated learning on teaching placement in schools in the UK. The discussion focuses on the impact that the use of new technology may have on established practices for assessment and models of supervision. Consideration is given to how the use of such technology may enable new pedagogical pathways with particular reference to reflective practice and self-assessment. The findings from a specialist Teacher Education programme (Deaf Education) within this study have direct implications for practice-based learning, both within teacher preparation programmes and in the wider field of professional practice.